Women of color in higher education turbulent past, promising future - Jean-Marie, Gaetane; Lloyd-Jones, Brenda (Bingley, U.K. : Emerald, 2011)
Historically, women of color have experienced discrimination based on the double jeopardy of race and/or ethnicity, and gender in their quest for access and advancement in higher education. Todays women of color in higher education however are the beneficiaries of courageous and committed women predecessors who confronted and disrupted institutions to attain a higher level of education (Jean-Marie, 2005). This two-edited volume focuses on African American, Hispanic American, Native American, and Asian-Pacific American women whose increased presence in senior level administrative and academic positions in higher education is transforming the political climate to be more inclusive of women of color. Topics include trends and issues, leadership styles/characteristics, tenure and promotion, mentoring/social networks, and challenges and opportunities. As a conceptual framework, the collection of chapters in the two volumes acquaints readers with a broad overview of the characteristics and experiences of women of color in higher education. The two volumes include: Women of Color in Higher Education: Turbulent Past, Promising Future, Women of Color in Higher Education: Contemporary Perspectives and Changing Directions.
Prologue / Jean Lau Chin -- Examining the'present' status of women of color / Brenda Lloyd-Jones -- ch. 1.'Unfinished agendas' : trends in women of color's status in higher education / Ga$1#0B(Bane Jean-Marie -- ch. 2. Women of color in higher education : feminist theoretical perspectives / Penny A. Pasque -- ch. 3. Women of color : their path to leadership makes for a better higher education for all / Leonard A. Valverde -- ch. 4. African American females' career paths to the presidency : navigating the glass ceiling challenge / Sandra L. Harris, Sandra Jackson Wright, Clementine Msengi -- ch. 5. Woman(ist)s' work : the experiences of black women scholars in education at predominantly white institutions / Erica D. McCray -- ch. 6. Your story is my story : examining the research literature on black women in teacher education / Monika Williams Shealey, Allyson Leggett Watson, Zhengyun Qian -- ch. 7. Black women faculty in educational leadership : unpacking their silence in research / April L. Peters -- ch. 8. Advocacy in the hyphen : perspectives from Latina Junior Faculty at a Hispanic-serving institution / Anne-Marie Nu{u4BA5}z, Elizabeth Murakami-Ramalho -- ch. 9. From doctoral students to faculty : Chicanas' articulation with trauma in academe / Gloria H. Cu{u2864}raz -- ch. 10. Hispanic women administrators : self-efficacy factors that influence barriers to their success / Carmen L. Suez-McCrink -- ch. 11. Latina presidents : making a difference at Hispanic-serving institutions / Juanita Gamez Vargas -- ch. 12. Tribal colleges : cultural support for women campus presidencies / Bernita L. Krumm, Wayne Johnson -- ch. 13. Identity and research : exploring themes of scholarship of an American Indian scholar in the academy / Hollie Mackey -- ch. 14. Asian American women faculty and the contested space of the classroom : navigating student resistance and (re)claiming authority and their rightful place / Shirley Hune -- ch. 15. Few and far between : exploring the experiences of Asian American and Pacific Islander women in student affairs administration / Dina C. Maramba -- Epilogue / Carol Logan Patitu.s
Includes indexes.
Keywords: Sex discrimination in higher education; Women -- Education (Higher)